2005
DOI: 10.1158/1055-9965.epi-04-0410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Papillomavirus Messenger RNA and DNA Detection: A Cross-sectional Study of 4,136 Women >30 Years of Age with a 2-Year Follow-up of High-Grade Squamous Intraepithelial Lesion

Abstract: The purpose of this study was to compare the detection of human papillomavirus (HPV) DNA with detection of mRNA. The study included 4,136 women >30 years of age. E6/E7 mRNA expression from the carcinogenic HPV types 16, 18, 31, 33, and 45 was detected by the PreTect HPVProofer assay, whereas the presence of HPV DNA was detected by Gp5+/6+ consensus PCR followed by typespecific PCR. A total of 4.0% had an abnormal cytologic diagnosis, 3.0% were positive by PreTect HPV-Proofer, 4.4% by type-specific PCR, and 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
5
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 35 publications
(36 reference statements)
7
95
5
4
Order By: Relevance
“…The high levels of E6/E7 expression in CIN which we observed appear to be contradictory to the data obtained in several other studies (Falcinelli et al, 1993;Riethdorf et al, 2001;Sotlar et al, 2004;Molden et al, 2005;Andersson et al, 2006). The most probable explanation for this is the sampling strategy used (biopsies versus cervical scrapes).…”
Section: Figurecontrasting
confidence: 99%
“…The high levels of E6/E7 expression in CIN which we observed appear to be contradictory to the data obtained in several other studies (Falcinelli et al, 1993;Riethdorf et al, 2001;Sotlar et al, 2004;Molden et al, 2005;Andersson et al, 2006). The most probable explanation for this is the sampling strategy used (biopsies versus cervical scrapes).…”
Section: Figurecontrasting
confidence: 99%
“…No other species of HPV was detected by PCR amplification followed by DNA sequencing in these particular biopsies. This does not reflect the distribution of HPV in Norwegian tumour samples reported by others, although HPV16 is reported to be the most common high-risk HPV in Norwegian specimens, accounting for more than 50% of all cases (Kraus et al, 2004;Molden et al, 2005). Owing to the technical limitation of the PCR/sequencing assay, we neither can exclude the presence of other subspecies of HPV within our samples, nor can we exclude the presence of viral variants, sequence disruptions or very low HPV levels that escaped detection by the methods used.…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, HPV DNA results were positive in about three times more samples than E6/E7 mRNA expression. Studying women under the age of 30 years, Molden et al (30) observed HPV E6/ E7 mRNA expression in approximately two out of three HPV DNA positive women, being similar to the findings observed for women older than 30 years (31) . In our study, 60% of the CIN2+ samples were positive for E6/ E7 mRNA.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, HPV types are classified as high-risk (HR) or low-risk (LR) according to the risk of cancer in the infected hosts. The most common HR types are 16,18,31,33,45, which are detected in > 85% of the carcinomas worldwide (8) .…”
Section: Introductionmentioning
confidence: 99%